2022
DOI: 10.1128/aem.02185-21
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characteristics of the Transmissible Locus of Stress Tolerance (tLST) and tLST Harboring Escherichia coli as Revealed by Large-Scale Genomic Analysis

Abstract: This study, through a large-scale genomic analysis, demonstrated that the genomic island tLST related to multiple stress resistance (such as extreme heat resistance and oxidative stress tolerance) in E. coli is differentially present in subgroups of E. coli and is strongly associated with certain phylogenetic background of the host strain. The study also shows the transmission mechanisms of tLST in E. coli and other bacterial species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In addition to the two full operons ato and ydj , the xap and fec operons were partially overrepresented in the acid-resistant E. coli . The differences in prevalence among xap or fec genes could have arisen from various factors such as loss/gain of genes or limitations of draft genomes ( 41 ). The xap genes involved in the xanthosine metabolism allow E. coli to utilize purine nucleoside as a carbon source ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the two full operons ato and ydj , the xap and fec operons were partially overrepresented in the acid-resistant E. coli . The differences in prevalence among xap or fec genes could have arisen from various factors such as loss/gain of genes or limitations of draft genomes ( 41 ). The xap genes involved in the xanthosine metabolism allow E. coli to utilize purine nucleoside as a carbon source ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong environmental adaptation and recurrent transition between environmental niches ( 56 ) likely lead to the abundance of phylogroup B1 in the environment. On the other hand, E. coli has a high genome plasticity/diversity, with <10% of the pan-genome being core genes ( 25 ) and distinct accessory genomes in phylogroups revealed by large-scale genomic analyses ( 26 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that heat is more effective than treatment using UVC for the sterilization of N95 masks. 17 Bacteria's walls composed of protein have thermophobia characteristics. High temperatures will cause denaturation of these proteins and result in the death of these microorganisms.…”
Section: Aerosol Penetration and Air Resistance Testmentioning
confidence: 99%
“…For instance, the phylogroup B1 E. coli has a much higher survival rate and prevalence in fresh water, compared to other phylogroups ( 21 , 25 ). The distribution of a genomic island, namely, the transmissible locus of stress tolerance (tLST), is primarily concentrated in phylogroup A E. coli ( 26 ). Information on the relationship between the phylogenetic background and the biofilm forming ability of E. coli seems largely lacking.…”
Section: Introductionmentioning
confidence: 99%